PENGANGGARAN MODAL PERUSAHAAN MULTINASIONAL CORPORATION (MNC) - Muammar Khadafi; Leni Putri Ramadhani; Nur Shabrina; Agus Pitriana; Mutiara Zairah (PT. Hasba Edukasi Mandiri, 2025)
Capital budgeting is a crucial process in long-term investment decision-making, particularly for multinational corporations (MNCs) operating across borders. Unlike domestic companies, MNCs face additional complexities such as differences in currency exchange rates, cross-border tax policies, profit repatriation restrictions, political risk, and differing perspectives between parent and subsidiary companies. This paper aims to explain the concept of capital budgeting in MNCs, the differences in analysis from the parent and subsidiary perspectives, the profit repatriation mechanism, and the key factors to consider in evaluating international projects. The analytical method used focuses on the Net Present Value (NPV) approach, taking into account after-tax cash flows, exchange rates, and risk-adjusted rates of return. Through conceptual discussions and case studies, this paper demonstrates that investment decisions that appear feasible from the subsidiary’s perspective may not necessarily be profitable for the parent company. Therefore, MNC capital budgeting must be conducted comprehensively, emphasizing value creation for the parent company and its shareholders as a whole.